Helicobacter pylori infection perturbs iron homeostasis in gastric epithelial cells. - Sebastian E Flores; Alan Aitchison; Andrew S Day; Jacqueline I Keenan (PLoS ONE)
The iron deficiency anaemia that often accompanies infection with Helicobacter pylori may reflect increased uptake of iron into gastric epithelial cells. Here we show an infection-associated increase in total intracellular iron levels was associated with the redistribution of the transferrin receptor from the cell cytosol to the cell surface, and with increased levels of ferritin, an intracellular iron storage protein that corresponded with a significant increase in lysosomal stores of labile iron. In contrast, the pool of cytosolic labile iron was significantly decreased in infected cells. These changes in intracellular iron distribution were associated with the uptake and trafficking of H. pylori through the cells, and enhanced in strains capable of expressing the cagA virulence gene. We speculate that degradation of lysosomal ferritin may facilitate H. pylori pathogenesis, in addition to contributing to bacterial persistence in the human stomach.